Environment as a cultural and economic “barrier” of Canada - Ivanović Mirko (Glasnik Srpskog Geografskog Društva)
The aim of this paper is to show to what extent natural conditions and environment are a factor in the distribution of population in Canada and their division into north and south. How it historically affected the different cultural and economic development of Canada, the deep regionalism between the North and the South. How much that modern climate change has an affect on “opening” the region of North Canada (the territories of Nunavut, Yukon and Northwest territories). By analyzing climate tables and maps and comparing them, we conclude about the magnitude of climate changes that have occurred in that region in the last few years and decades and their positive and negative effects on the local population. The results showed that this historical "barrier" of the region is slowly "melting" with the ice. This paper is significant for two reasons, the first is to explain the historical division of the country through natural conditions as the main factors of division (into the southern more populated part and the northern sparsely populated part of Canada) and second to show how climate change really changes the everyday life of the local population in a positive (economic growth and employment) and negative (environmental change due to climate change and environmental pollution due to the arrival of industry in those "remote" areas) aspect.